A review on chinese herbal medicine used as carminative - Amitava Kabiraj; Rohitas Deshmukh (Elsevier, 2024)
Introduction: The World Health Organization (WHO) recognizes traditional medicine's diverse practices, including herbal remedies, as a significant component of global healthcare. Traditional Chinese Medicine (TCM), originating over 3,000 years ago, incorporates herbal medicine, acupuncture, and other techniques. The term ''carminative'' is derived from the Latin word ''carminare,'' meaning to cleanse. Carminatives can reduce lower esophageal pressure, thereby potentially increasing the susceptibility to gastroesophageal reflux disease or heartburn. Methods: The online databases including Scopus, PubMed, Web of Science, and Google Scholar were searched using different via keywords: Carminatives, Chinese herb, and Herbal. The objective of this review was to provide a concise summary of the herbal ingredients that have been previously documented for their gastro-stimulating properties in carminative products. Results: Medicinal plants are widely recognized as a crucial and valuable resource for the development of pharmaceutical products. These herbal products possess carminative properties and offer additional health benefits in a wide range of therapeutic uses of carminative like as Anti-microbial, Diuretic, Irritable bowel syndrome, etc. Discussion: With the increasing global interest in natural medicines, there is a potential for higher demand for TCM as carminatives. Novel formulations with a blend of TCM can be created to improve their effectiveness and convenience. This review can provide chances for more research and increase understanding of TCM for usage as a carminative. Conclusion: In conclusion traditional Chinese Medicine (TCM) incorporates herbal remedies, like those with carminative properties, to address gastrointestinal discomfort and promote overall well-being. TCM's global popularity reflects its effectiveness in integrating herbal medicine, acupuncture, and other techniques. The use of carminatives in TCM aligns with their historical role in relieving digestive issues and promoting balance in bodily humors.